Relationships between frequency of contact, role meaning, and intergenerational solidarity in grandparental role satisfaction in Kermanshah, Iran - Seifali, Shahla (2013)
The purpose of study is to examine the relationships between frequency of contact, role meaning and intergenerational solidarity with grandparent role satisfaction. A cross-sectional design was employed to determine factors that predict grandparent role satisfaction among grandparents aged 60 and above with a noncoresident grandchild aged 12 to 17 in Kermanshah, Iran. A total of 290 grandparents were recruited using a two-stage proportionate random sampling technique to obtain a representative sample. The standardized questionnaire used in this study included items on the frequency of contact, role meaning,intergenerational solidarity, and role satisfaction as well as questions measuring grandparent, parents and grandchildren’s sociodemographic characteristics. There were 66.2% grandmothers and 33.8% grandfathers in the sample with a mean age 67.55 (SD = 5.72). The majority of respondents attributed meaning to their grandparent role (76.2%) and reported satisfaction with the role (98.4%). Most of the respondents reported high level of intergenerational solidarity (91.7%). The regression model predicting role satisfaction was significant (F21,101 = 5.485) indicates 53% of the variance in role satisfaction being explained by age of becoming grandparent (β =.17), income of grandparent (β = -.16), distance (β = .16), frequency of contact (β = .35) and role meaning (β = .58). The results of a three-step multiple regression analysis and Sobel-test (t = 2.30,p≤.05) indicated that the positive effects of role meaning on role satisfaction is significantly mediated by intergenerational solidarity. The results indicated the importance of frequency of contact, role meaning, and intergenerational solidarity on the role satisfaction of Iranian grandparents. These findings implied that grandparent role satisfaction is achieved through increased interaction with grandchildren, and thus, it is important to ensure that intergenerational contact is encouraged in today’s families.